multiply :-
(2y+ 3x) (3y-2x)
Answers
Answered by
26
We have,
![\quad \: (2y + 3x)(3y - 2x) \\ \\ = 2y(3y - 2x) + 3x(3y - 2x) \\ \\ = 6 {y}^{2} - 4xy + 3xy - 2 {x}^{2} \\ \\ = 6 {y}^{2} - xy - 2 {x}^{2} \quad \: (2y + 3x)(3y - 2x) \\ \\ = 2y(3y - 2x) + 3x(3y - 2x) \\ \\ = 6 {y}^{2} - 4xy + 3xy - 2 {x}^{2} \\ \\ = 6 {y}^{2} - xy - 2 {x}^{2}](https://tex.z-dn.net/?f=+%5Cquad+%5C%3A+%282y+%2B+3x%29%283y+-+2x%29+%5C%5C++%5C%5C++%3D+2y%283y+-+2x%29+%2B+3x%283y+-+2x%29+%5C%5C++%5C%5C++%3D+6+%7By%7D%5E%7B2%7D++-+4xy+%2B+3xy+-+2+%7Bx%7D%5E%7B2%7D++%5C%5C++%5C%5C++%3D+6+%7By%7D%5E%7B2%7D++-+xy+-+2+%7Bx%7D%5E%7B2%7D+)
Answered by
0
Answer:
6y^2+5xy-6x^2
Step-by-step explanation:
2y(3y-2x)+3x(3y-2x) = 6y^2+5xy-6x^2
Similar questions